Trends in systemic lupus erythematosus mortality in Spain from 1981 to 2010. (April 2014) - Ruiz, E; Ramalle-Gómara, E; Elena, Á; Quiñones, C; Alonso, V; Posada, M; ,
Background: Incidence and mortality of systemic lupus erythematosus (SLE) seem to be increasing in the last few decades, in contrast to the survival rate that has improved over time. The objective of this study was to examine the trends in the SLE mortality in Spain over a 30-year period (1981–2010). Methods: Data on SLE deaths were drawn from the National Statistics Institute of Spain. Crude and overall age-standardized SLE mortality rates were calculated and joinpoint regression models were used to describe trend changes. Mean age of deaths by SLE each year was also assessed. Results: The overall age-standardized SLE mortality rate was 1.82 per million in 1981 and 2.24 in 2010. It was higher in women, 1.39 vs 0.43 in 1981 and 1.96 vs 0.28 in 2010. There was a statistically significant change in 1999. The overall age-standardized mortality rate increased from 1981 to 1999 and stabilized from 2000 to 2010. Only male rates decreased from 2000 to 2010. The mean age at death increased with time, from 42 years in 1981 to 61 years in 2010. Conclusions: In conclusion, a slight decrease in SLE mortality has been observed in Spain over the last decade and future studies would be needed to explain the factors contributing to the improvement in the mortality rates.